ANALISIS SADD ADH DHARI’AH TERHADAP KETENTUAN PBI 13/23/2011 TENTANG PENERAPAN MANAJEMEN RISIKO BANK UMUM SYARIAH DAN UNIT USAHA SYARIAH - Maimunah Datul Yasar (Maliyah : Jurnal Hukum Bisnis Islam, 2015)
The provisions are used to analyze whether there is a match on 10 risk in the provision of PBI 13/23/2011 About the Risk Management Implementation Islamic Banks and Sharia Business unit. On Risk Management Islamic Banks and Sharia Business unit. This mindset rests on theories sadd al-dhar>iah then associated with the provision of PBI 13/23/2011 About the Application of Risk Management Commercial Bank Sharia and Unit of a special nature. The results showed that the implementation of risk management provisions 13/23/2011 About the Application of Risk Management for Islamic Banks and Sharia Business Unit stipulated in Article 2, 3, 12, and 13. in the application of risk management is no risk 8 of 10 Islamic banks risk adopted from conventional banks, according to the 8 risk of exposure that can be applied to conventional banks in Islamic banks with risk management provisions should be operational by the principles of sharia.